Job satisfaction among hotel employees: analyzing selected antecedents and job outcomes. A case study from Poland - Grobelna, Aleksandra; Sidorkiewicz, Marta; Tokarz-Kocik, Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
This study examines selected antecedents of hotel employees’ job satisfaction and its critical consequences which are crucial for both individuals and hotel organizations as a whole. Specifically this study investigates the effects of individual and job characteristics on employees’ job satisfaction and the effect of job satisfaction on employees’ affective organizational commitment and intention to leave. Therefore, a survey instrument was used to collect information from 11 hotels in northern Poland. A total of 356 hotel employees agreed to participate in the study. The results of structural equation modelling proved that intrinsic motivation, supervisor support, role conflict and role ambiguity are all significant predictors of hotel employees’ job satisfaction. Job satisfaction, in turn, has been found to be directly and positively associated with affective organization commitment and negatively with turnover intention, however its direct impact on affective commitment was strongest. Research discussion, implications of the results and directions for future studies are also provided
Argumenta Oeconomica, 2016, Nr 2 (37), s. 281-310
Keywords: hospitality industry; hotel employees; job satisfaction; affective organizational commitment; intention to leave